Mutasi pada Beberapa Kandidat Galur Mutan Pemulih Kesuburan Tanaman Padi - , Sobrizal (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2007)
Cytoplasmic male sterility (CMS) system has largely been applied in development of rice hybrid varieties. In this system the maintainer and restorer lines are necessary to maintain the CMS and to restore the pollination abilities of hybrid plants, respectively. In this study, rice candidate of restorer mutant lines were developed through irradiation of CMS seeds by 0.2 kGy gamma rays. Some mutations indicated by polymorphism between mutants and original plants were observed through simple sequence repeat (SSR) marker genome survey in six mutant lines. Frequencies of polymorphism varied depend on the lines, range from 8.5 to 18.3%. No common marker showed polymorphism between six mutant lines and original plants indicating that the mutant lines do not carry the same restoring genes. Nevertheless, allelic tests or linkage studies using segregating populations are needed for confirmation. This result should be useful as initial information on genetic studies of restoring genes induced by gamma ray irradiation as well as for application of these genes in hybrid rice breeding program.   Key words :  Mutation, restorer mutant lines, hybrid rice